Calixarene based nanocomposite materials for high-performance supercapacitor electrode. (10th August 2017) - Waghmode, Babasaheb J.; Soni, Roby; Patil, Kashinath R.; Malkhede, Dipalee D.
Abstract : Stability of 2D MoS2 nanomaterial is due to cage structure of SC6 and it acts as an active nucleation site for anchoring PANI nanostructure. Calixarene plays a positive synergistic effect in MoS2 and PANI by improvement of overall electrochemical performance. Abstract : A functionalised calixarene 4-sulphatocalix[6]arene hydrate (SC6) stabilises MoS2 /partially reduced graphene oxide (rGO) nanosheet. Such stabilised SC6–rGO/SC6–MoS2 and SC6 doped polyaniline (PANI) together form a nanocomposite hybrid material for supercapacitor electrodes. The nanocomposite is fabricated by an in situ polymerization method. Transmission electron microscopy (TEM) results suggest that PANI nanostructures grow homogeneously on the surfaces of SC6 functionalised MoS2 . Calixarene acts as a dopant for PANI as well as a stabiliser for the 2D nanosheets of rGO/MoS2 . The characterisation of composites and the basic components is done using various techniques, namely, solid-state FT-IR spectroscopy, X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD). The electrochemical performance is analysed by cyclic voltammetry (CV), galvanostatic charge/discharge and electrochemical impedance spectrometry (EIS). It is found that the SC6 functionalised MoS2 and SC6 doped PANI form a uniform nanocomposite. The synthesised composites show high specific capacitance (691 F g −1 ) and good cycling stability during charge–discharge process when used as supercapacitor electrodes. The improvement in electrochemical performance of composites is assigned to synergistic effect of SC6 stabilised MoS2 and doped PANI. Our investigation highlights the importance of use of calixarene in composites for improved supercapacitor performance. The role of calixarene in the present study paves the way for the application of alike materials in composite supercapacitors for energy storage applications.